Nesoressa crawfordi, n. gen., n. sp., a montane island milliped in New Mexico, USA; proposal of the new tribe Nesoressini and a preliminary cladogram of the lineage "Aniulina" (Julida: Parajulidae) - Shelley, Rowland M.; Medrano, Michael F. (Zootaxa, 2006)
Nesoressa crawfordi, n. gen., n. sp., is proposed for a slender parajulid milliped inhabiting high elevation boreal forests on five inselberg mountains in Cibola and Socorro counties, New Mexico; it is anatomically incompatible with established tribes, so Nesoressini, n. tribe, is erected to accommodate it. A sixth population existed 27 years ago in "caves near ice caves," Cibola County, but its presence today awaits confirmation. In addition to nemasomatid-like body dimensions, N. crawfordi is characterized by an elevated pleurotergal "shield" on the caudal margin of the gonopodal aperture, simple anterior gonopods possessing a sternum, telopodites, & large coxal lobes, and posterior gonopod (pg) telopodites comprising three closely appressed projections— long, parallel, nearly identically configured prefemoral processes & solenomeres and shorter, spiniform branches "C." The disjunct populations of N. crawfordi appear to be relicts from a continuous Pleistocene population in central New Mexico that fragmented into localized vicariants as the climate warmed and dried in the post-Pleistocene era. As the pgs are joined by a sclerotized sternum, Nesoressa/Nesoressini appears to be the sister-group to a clade consisting of tribes lacking this structure. A clade "Aniulina" is postulated comprising Nesoressini + (Parajulini + (Aniulini + Gosiulini)) that originated in the Rio Grande border region of the US and Mexico, its present center of diversity. Apacheiulus Loomis, 1968, a potential synonym of Gosiulus Chamberlin, 1940, is assigned to the Gosiulini, and the tribes Bollmaniulini & Karteroiulini, both established by Causey, 1974, are tentatively regarded as synonymous.